3 – (–3) + 7 – 4 =

3 – (–3) + 7 – 4 = 3 + 3 + 7 - 4 = 6 + 7 - 4 = 13 - 4 = 9

Question|Asked by francybadinga

Asked 12/12/2017 12:09:51 PM

Updated 12/12/2017 2:12:30 PM

1 Answer/Comment

Edited by Masamune [12/12/2017 2:11:49 PM]

g
googletag.cmd.push(function() { googletag.display('div-gpt-ad-1564665647093-0'); });

Rating

8

3 – (–3) + 7 – 4

= 3 + 3 + 7 - 4

= 6 + 7 - 4

= 13 - 4

= 9

= 3 + 3 + 7 - 4

= 6 + 7 - 4

= 13 - 4

= 9

Added 12/12/2017 2:12:30 PM

This answer has been confirmed as correct and helpful.

Solve the following system by any method.
–3x + 5y = –9
4x + 8y = 12

Question|Asked by francybadinga

Updated 12/13/2017 9:04:17 AM

1 Answer/Comment

–3x + 5y = –9

4x + 8y = 12

(–3x + 5y = –9) * (4)

-12x + 20 = -36

(4x + 8y = 12) * (3)

12x + 24y = 36

(-12x + 20 = -36) + (12x + 24y = 36)

44y = 0

y = 0

–3x + 5(0) = –9

-3x = -9

x = -9/-3

x = 3

Solution set: (3, 0)

4x + 8y = 12

(–3x + 5y = –9) * (4)

-12x + 20 = -36

(4x + 8y = 12) * (3)

12x + 24y = 36

(-12x + 20 = -36) + (12x + 24y = 36)

44y = 0

y = 0

–3x + 5(0) = –9

-3x = -9

x = -9/-3

x = 3

Solution set: (3, 0)

Added 12/13/2017 9:04:17 AM

This answer has been confirmed as correct and helpful.

34,461,083

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 768 [Total 6641] Ratings 16 Comments 608 Invitations 0 Offline

There are no comments.